Spinal muscular dystrophy–a revisit of the diagnosis and treatment modalities - Srivastava G.; Srivastava P. (My University, 2025)
Spinal Muscular Atrophy (SMA) is a pan-ethnic disorder and generally characterized as prevalent lethal genetic disease of infants. It is an autosomal recessive neuromuscular disease caused by degeneration of alpha motor neurons in the spinal cord, resulting in progressive proximal muscle weakness and paralysis. Due to the high carrier frequency (1:50), the burden of this genetic disorder is very heavy in developing countries. Till date no absolute cure or effective treatment of the disease is available in clinical practice, whereas minor enhancement of SMN protein levels can be beneficial. It can be achieved by augmenting SMN2 transcription, stimulating exon 7 splicing and protein stabilization. Due to its low prevalence among population, costly screening and diagnosis, the disease is still lacking proper management. SMN is expressed almost in all tissues of body, still the reason why only lower motor neurons are affected in SMA is unknown. Research is still going on and with advancement of innovative therapies and gene modification, improved outcome may come in near future. Presently, supportive care including respiratory, nutritional, psychiatric and orthopaedic management can ameliorate clinical symptoms and improve survival rates if SMA is diagnosed early in life. Routine prenatal and new-born screening can help with potential benefits and timely management. In this review, the concept of newer methodological system and recent advances for molecular diagnosis of SMA with the variability in the clinical features is stressed. The public health community should remain alert to the rapidly changing developments in early detection and treatment of SMA. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.